Pengaruh Circuit Training terhadap Perubahan Komposisi Tubuh pada Individu Overweight - Indah Rumekti; Agus Pribadi; Priska Dyana Kristi; Andri Arif Kustiawan (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This research is driven by the high prevalence of overweight conditions, which pose risks for metabolic disorders and functional physical decline. This study aims to analyze the effect of circuit training on body composition changes among overweight individuals. Employing a quantitative approach with a pre-experimental one-group pretest-posttest design, this study involved overweight participants selected through a purposive sampling technique. Body composition measurements including body weight, body mass index (BMI), and body fat percentage were conducted before and after an eight-week exercise program intervention. Statistical analysis revealed a significant decrease in body weight, BMI, and body fat percentage following the exercise intervention. The physiological mechanisms of circuit training proved effective in optimizing energy expenditure and elevating post-exercise metabolic rates. In conclusion, circuit training is effective in improving body composition among overweight individuals. The implication of this study suggests that circuit training can be recommended as a safe, efficient, and structured exercise strategy for weight management and body fat reduction.